Kedudukan dan Keabsahan Hukum Perjanjian Joint Venture dalam Hukum Perdata Indonesia - Rafika Amalia; I Putu Edi Rusmana (Universitas Batanghari Jambi, 2025)
The joint venture agreement is a form of business collaboration increasingly utilized in commercial practice by both domestic and foreign parties. However, Indonesian legislation does not explicitly regulate such agreements, raising legal questions regarding their standing and enforceability under national law. This study aims to examine the legal position of joint venture agreements within the Indonesian civil law system and assess their compliance with the validity requirements of contracts as stipulated in Article 1320 of the Indonesian Civil Code (KUH Perdata). This is normative legal research employing a statute-based and conceptual approach. The findings show that joint venture agreements are legally acknowledged and enforceable based on the principle of freedom of contract as articulated in Article 1338 of the Civil Code As long as the agreement meets the four requirements for a valid agreement, namely agreement, capacity, a specific object, and a lawful cause it is considered valid and binding under Indonesian civil law. Although there is no specific statutory framework governing joint ventures, their legal force is supported through legal doctrines and judicial precedents. This study concludes that the absence of explicit regulation does not invalidate joint venture agreements but highlights the importance of carefully interpreting foundational civil law principles to ensure legal certainty and protection for the contracting parties.